2017
DOI: 10.1111/1475-6773.12670
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Readmission and Social Risk Factors Identified from Physician Notes

Abstract: Objective To evaluate the prevalence of seven social factors using physician notes as compared to claims and structured electronic health records (EHRs) data and the resulting association with 30‐day readmissions. Study Setting A multihospital academic health system in southeastern Massachusetts. Study Design An observational study of 49,319 patients with cardiovascular disease admitted from January 1, 2011, to December 31, 2013, using multivariable logistic regression to adjust for patient characteristics. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(135 citation statements)
references
References 70 publications
6
127
1
1
Order By: Relevance
“…However, these variables did not predict readmission rates maybe because risk of readmission is determined by social as well as medical factors 16. Information on other recognised prognostic criteria such as Sequential Organ Failure Assessment Score (SOFA) were not available 17.…”
Section: Discussionmentioning
confidence: 99%
“…However, these variables did not predict readmission rates maybe because risk of readmission is determined by social as well as medical factors 16. Information on other recognised prognostic criteria such as Sequential Organ Failure Assessment Score (SOFA) were not available 17.…”
Section: Discussionmentioning
confidence: 99%
“…For the latter two characteristics, we constructed binary measures denoting whether respondents were unmarried or had a high school education or less (vs some postsecondary education or higher). Education and marriage have well‐documented relationships with health and outcomes of care, including hospital readmissions and mortality …”
Section: Methodsmentioning
confidence: 99%
“…(30). Some studies specified that a combination of both structured and unstructured SDOH data were contained in EHRs (12,31,32).…”
Section: Contextmentioning
confidence: 99%
“…No health system had a fully automated collection process, although automation was relevant to collection processes through the use of digital devices for gathering patient information. While this review did not specifically focus on practices beyond collection, our collected articles addressed health care staff's preference for free-text notes over questionnaires (12), as well as the possibility for Natural Language Processing (NLP) algorithms to efficiently and reliably identify SDOH data (29,32,34). One study revealed that data extracted from clinical notes were more comprehensive than data extracted from screening questionnaires (32).…”
Section: Automation In Data Collection Toolsmentioning
confidence: 99%